1992
DOI: 10.1111/j.1532-5415.1992.tb02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Non‐Demented Older Adults with Hypothyroidism

Abstract: Hypothyroidism in non-demented older adults is associated with impairments in learning, word fluency, visual-spatial abilities, and some aspect of attention, visual scanning, and motor speed. The MMS by itself was sensitive in differentiating hypothyroid patients with cognitive deficits from controls, while electrophysiological measures did not generally differentiate the hypothyroid patients from normal controls. The MMS was not sensitive to treatment effects, but treatment was associated with significant imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
167
4
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(186 citation statements)
references
References 43 publications
11
167
4
3
Order By: Relevance
“…We found that in a sample of 122 healthy, euthyroid women with mean age of 51 years, higher levels of fT3 and TgAB levels within the normal range were correlated with slower performance and more errors on tests of executive function. It has been previously reported that mild hypothyroidism can cause significant worsening of information processing speed, reduced efficiency in executive functions, and poorer learning (Osterweil et al, 1992;Haggerty et al, 1993;Baldini et al, 1997;Kalmijn et al, 2000;Zhu et al, 2006). Our results therefore demonstrate a similar relationship between higher levels of fT3 and TgAB within the normal range and tests of executive functions in healthy euthyroid women.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We found that in a sample of 122 healthy, euthyroid women with mean age of 51 years, higher levels of fT3 and TgAB levels within the normal range were correlated with slower performance and more errors on tests of executive function. It has been previously reported that mild hypothyroidism can cause significant worsening of information processing speed, reduced efficiency in executive functions, and poorer learning (Osterweil et al, 1992;Haggerty et al, 1993;Baldini et al, 1997;Kalmijn et al, 2000;Zhu et al, 2006). Our results therefore demonstrate a similar relationship between higher levels of fT3 and TgAB within the normal range and tests of executive functions in healthy euthyroid women.…”
Section: Discussionsupporting
confidence: 74%
“…For example, in an fMRI study that examined blood oxygen level-dependent (BOLD) responses to performance on various cognitive tasks, Zhu et al (2006) found that working memory deficits and executive dysfunctions in subclinical hypothyroid patients were reversed after 6 months of treatment with exogenous T4 (or L-thyroxine, LT4). Others have reported that treatment with LT4 significantly reduced cognitive and mood symptoms in both clinically hypothyroid elderly individuals (Osterweil et al, 1992) and in younger, subclinically hypothyroid individuals (Nystrom et al, 1988;Monzani, et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothyroidism has been reported to affect cognitive function and depressed mood [22,23]. Although it is still controversial whether subclinical hypothyroidism is associated with depression or cognitive dysfunction [24,25], it seems possible that disability and/or depressed mood due to endocrinological dysfunction could decrease the physical activity of daily life, which may result in the reduction of mechanical load on heel.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these changes are irreversible and permanent (Di Liegro, 2008;Henrichs et al, 2010;Noda, 2015). More importantly, there are several psychiatric symptoms during the hypothyroidism such as anergia, psychosis, mania, apathy, mood instability, hypersomnia, dementia (Osterweil et al, 1992;Goh et al, 2014), attentional abnormalities and delaying the psychomotor (Awad, 2000). These symptoms with the cognitive impairment might be increased with the age progress (Mallett et al, 1995;Dugbartey, 1998).…”
Section: Commentarymentioning
confidence: 99%